The effect of using a proposed educational tool according to some variables Eikinmetekal to develop the skill of learning performance transmitter in tennis - Sattar, Hasnaa (Journal of Physical Education, 2014)
The research aims to help prepare the tool according to some variables kinematical and to identify the effect of to developing learning used to perform the skill serve in a sample search. The sample consisted of (40) female student and the most important conclusions of the use of tools to help according to some variables kinematical has a key role in the evolution of performance skill flat serve to the research group and constant repetition and varied exercises using utilities increases the excitability of the female students of the evolution towards better performance in the skill and the researcher recommended the using of aiding tools to development of technical skills and invest all available ones and invent many of the tools and aids that work on the development of other technical skills